PENINGKATAN EKONOMI KEUARGA DENGAN DAUR ULANG BARANG BEKAS - Dewi Nurjannah; Fien Zulfikarijah; Eko Handayanto (Bajang Institute, 2025)
The community service activities carried out aim to foster an entrepreneurial spirit among households as an effort to improve the economy of families in the Gading Kasri sub-district. In addition, it also aims to encourage the surrounding community to be aware of maintaining environmental cleanliness and health, as well as the need for proper waste management. The community service methods included counseling, discussions, question and answer sessions, and hands-on practice in processing used items into items with added economic value. The results of this activity, which was attended by 15 representatives of PKK members, are expected to contribute to improving the economy of PKK mothers, to share knowledge, and to encourage the community to develop their resources in a sustainable manner to improve the family economy. This effort to recycle used items, specifically plastic waste, is intended to motivate the community to improve their abilities and skills and to work to bring benefits to themselves and the surrounding community by producing recycled plastic products such as flower vases, plastic flowers, wall decorations, and others.